A Standardized Method for Extraction of Parada (Mercury) from Hingula (Cinnabar) with the help of Modified Nada-Yantra (International Journal of Ayurveda and Pharma Research, 2024)
Background: Parada (mercury) has both, miraculous therapeutics effects as well as mythical importance. Naturally obtained mercury contains so many impurities, so extraction of mercury from Hingula (cinnabar) is comparatively easy and cheaper method, also it is suitable for further preparation of formulations. In classics it is mentioned that it as beneficial as Ashtasansakrita Parada (mercury which has processed with eight procedures). About 18 methods found in classics to obtain mercury from Hingula such as Urdhwapatana (upward sublimation), Adhoptana (downward sublimation), Tiryakapatana (distillation). The Urdhwapatana method with the help of Nada-Yantra (pitcher instrument) is mentioned in classics but due to some lacunas mercury after dissociation get lost in form of fumes which causes less yield and researcher may have some hazardous effects because of toxicity of mercuric fumes. Objective: To develop a standardized method to extract Parada from Hingula through which maximum yield can be obtained and chances of harm and loss can be minimized. Material & Method: In this pharmaceutical research work we tried to modify classical procedure of Hingullotha Parada through Nada- yantra and evaluated its SOP. Result: With this modified method, mercury containing fumes get reduced and gained better yield (76.8%). Conclusion: Hingullotha Parada (collection of mercury from cinnabar) is considered as the best way to extract mercury, some small modifications in classical operating procedure can provide good yield as well as it is comparatively safer way.